2016
DOI: 10.3390/toxins8100296
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structure of Ribosome-Inactivating Protein Ricin A Chain in Complex with the C-Terminal Peptide of the Ribosomal Stalk Protein P2

Abstract: Ricin is a type 2 ribosome-inactivating protein (RIP), containing a catalytic A chain and a lectin-like B chain. It inhibits protein synthesis by depurinating the N-glycosidic bond at α-sarcin/ricin loop (SRL) of the 28S rRNA, which thereby prevents the binding of elongation factors to the GTPase activation center of the ribosome. Here, we present the 1.6 Å crystal structure of Ricin A chain (RTA) complexed to the C-terminal peptide of the ribosomal stalk protein P2, which plays a crucial role in specific reco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
77
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(79 citation statements)
references
References 36 publications
(46 reference statements)
0
77
2
Order By: Relevance
“…The C-terminal ends of the ribosomal stalk P proteins interact with a small well-defined hydrophobic pocket on the face of RTA opposite to the active site [ 27 , 28 ]. We show here that peptides derived from the conserved CTD of P proteins can disrupt RTA–ribosome interactions.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The C-terminal ends of the ribosomal stalk P proteins interact with a small well-defined hydrophobic pocket on the face of RTA opposite to the active site [ 27 , 28 ]. We show here that peptides derived from the conserved CTD of P proteins can disrupt RTA–ribosome interactions.…”
Section: Discussionmentioning
confidence: 99%
“…Although the amino acid sequences of the A1 subunit of Stx1 and Stx2 are only 21% and 20% identical to RTA, respectively, they are structurally and functionally very similar to RTA [ 26 ]. Recently, the structure of RTA together with the last six amino acids of P proteins was resolved by two different groups using different strategies (PDB IDs: 5GU4 and 5DDZ) [ 27 , 28 ]. Although 9-mer, 11-mer [ 27 ], or 10-mer [ 28 ] P stalk peptides were used in the studies, the structures resolved by both groups showed that only the last six residues interact with RTA.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The active form of RTA can selectively remove a single adenine from 28S rRNA. This results in further binding of elongation factor‐2 and blocking of protein synthesis, thereby causing cell death (Endo & Tsurugi, 1988; Shi et al, 2016).…”
Section: Introductionmentioning
confidence: 99%